Pregnancy Reclaimed: Art Therapy as Intervention for Depression and Anxiety - Wardi-Zonna, Katherine (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
Depression and related mental health disorders are common during pregnancy and the postpartum. Despite cautions against the use of psychotropic medication during pregnancy, many physicians continue to use medication as a frontline treatment. A number of theories have been put forth in an attempt to explain mental health struggles during pregnancy, yet there is inconclusive evidence that hormones or other physiological changes during pregnancy precipitate this occurrence. Instead, it is theorized that sociocultural factors are at the root of female struggle during pregnancy and into the postpartum. Women find themselves in a culture that sexualizes, commodifies, and medicalizes pregnancy then capriciously and callously evaluates and criticizes the postpregnancy recovery. For these reasons, art therapy is perfectly positioned to support the depression and anxiety symptoms experienced by women during pregnancy. If women during pregnancy are allowed opportunities to use the expressive arts for wellness, it is anticipated that this means of coping will carry over to the period of the postpartum and beyond.